Coyote at the kitchen door : living with wildlife in suburbia - DeStefano, Stephen, 1956- (Cambridge, Mass. : Harvard University Press, 2011)
"A moose frustrates commuters by wandering onto the highway; a cougar stalks his prey through suburban backyards; an alligator suns himself in a strip mall parking lot. Such stories, which regularly make headline news, highlight the blurred divide that now exists between civilization and wilderness." "In Coyote at the Kitchen Door, Stephen DeStefano draws on decades of experience as a biologist and conservationist to examine the interplay between urban sprawl and wayward wildlife. As he explores what our insatiable appetite for real estate means for the health and wellbeing of animals and ourselves, he highlights growing concerns, such as the loss of darkness at night because of light pollution. DeStefano writes movingly about the contrasts between constructed and natural environments and about the sometimes cherished, sometimes feared place that nature holds in our modern lives, as we cluster into cities yet show an increasing interest in the natural world." "Woven throughout the book is the story of one of the most successful species in North America: the coyote. Once restricted to the prairies of the West, this adaptable animal now inhabits most of North America - urban and wild alike. DeStefano traces a female coyote's movements along a winding path between landscapes in which her species learned to survive and flourish. Coyote at the Kitchen Door asks us to rethink the meaning of progress and create a new suburban wildlife ethic."--BOOK JACKET.
Prologue: Suburban beginnings -- The world's neighborhoods -- The form setter -- Gradient in time : a brief history of wildlife in America -- Suburban wildlife encounters -- Mixed messages -- The suburban jungle -- A trilogy of tolerable nuisances, part 1 : traffic -- A trilogy of tolerable nuisances, parts 2 and 3 : light and noise -- Home ownership and other near-death experiences -- A short story about a small moose -- Coyote spirits -- A suburban land ethic.
Includes bibliographical references and index.
Keywords: Urban animals; Coyote; Urbanization -- Environmental aspects